Analisis Perencanaan Pembeljaran Skills Lab Keperawatan Anak (Analysis Of Learning Plan Skills Lab Nursing Children) - Sulami .; Sri Mintarsih (Indonesian Journal on Medical Science, 2016)
Abstract: Learning plan is a draft or a preparation made by a lecturer, on learning that they are responsible before implementing learning, including the drafting of learning skills lab. The results of preliminary studies in Surakarta  Patria Husada Nursing Academy, the planning  of  learning nursing skills lab Child's still found a few problems, namely in the analysis of the learner and the environment and Learning Implementation Plan is not maximized presence and planning.This may affect the implementation of the learning laboratory (lab skills) are less than optimal and ultimately competence of learners is not reached(Depkes RI, 2000).This study aims to determine how the image on the planning of learning skills lab Child Nursing in Surakarta Patria Husada Nursing Academy.This research was conducted using qualitative descriptive research with case studies fixed (embedded case study research). Data collected by way of interviews, participant observation, document study and focus group discussion. Data processing is done by way of descriptive content (content analysis) using an interactive model that includes data collection, data reduction, data presentation and verification / conclusion.The results showed that in lesson planning nursing skills lab Kids in Surakarta Patria Husada Nursing Academy has been a practical guide books such as SOP (Standard Operating Procedure), syllabus and Learning Implementation Plan.  But in the analysis of the learner and the environment and Learning Implementation Plan, still not up existence and planning. Conclusion the planning of learning nursing skills lab children in Surakarta Patria Husada Nursing Academy, was well  planned in a structured and systematic, although not optimal in the presence of learning Implementation Plan, the analysis step learner and the environment.Keywords: Learning, Nursing, Planning, Skills lab Abstrak: Perencanaan pembelajaran merupakan sebuah rancangan atau persiapan yang dibuat oleh seorang dosen tentang pembelajaran yang menjadi tanggung jawabnya sebelum melaksanakan pembelajaran, termasuk di dalamnya adalah membuat rancangan pembelajaran skills lab. Dari Hasil studi pendahuluan di Akper Patria Husada Surakarta dalam perencanaan pembelajaran skills lab keperawatan Anak, masih ditemukan adanya beberapa masalah yaitu pada analisis pembelajar dan lingkungan serta Recana Pelaksanaan Pembelajaran(RPP) belum maksimal keberadaan dan perencanaannya. Hal ini dapat mempengaruhi pelaksanaan pembelajaran laboratorium (skills lab) yang kurang optimal dan pada akhirnya kompetensi peserta didik tidak tercapai (Depkes RI, 2000). Penelitian ini bertujuan untuk mengetahui bagaimana gambaran mengenai perencanaan pembelajaran skills lab Keperawatan Anak di Akper Patria Husada Surakarta. Penelitian ini dilakukan dengan menggunakan jenis penelitian deskriptif kualitatif dengan studi kasus terpancang(embedded case study research). Teknik pengumpulan data dilakukan dengan cara wawancara mendalam, observasi partisipatif, studi dokumen dan focus group discussion. Pengolahan data dilakukan dengan cara deskriptif isi(content analysis) dengan menggunakan model analisis interaktif yang meliputi pengumpulan data, reduksi data, penyajian data dan verifikasi/penarikan kesimpulan. Hasil penelitian menunjukkan bahwa dalam perencanaan pembelajaran skills lab keperawatan Anak di Akper Patria Husada Surakarta telah ada buku panduan praktikum berupa SOP(Standar Operasional Prosedur), silabus dan Rencana Pelaksanaan Pembelajaran(RPP). Namun dalam analisis pembelajar dan lingkungan serta Recana Pelaksanaan Pembelajaran(RPP) masih belum maksimal keberadaan dan perencanaannya. Kesimpulan perencanaan pembelajaran skills lab keperawatan anak di Akper Patria Husada Surakarta, sudah terencana dengan baik secara terstruktur dan sistematis, walaupun belum optimal pada keberadaan Rencana Pelaksaan pembelajaran (RPP), langkah analisis pembelajar dan lingkungan. Kata kunci: Keperawatan, Perencanaan, Pembelajaran, Skills lab.